A Conceptual Framework For Understanding Autonomy For Public Enterprises In India - Mascarenhas, R. C. (Academy of Management Journal, 1972)
This paper provides an operational framework to understand autonomy by examining the relationship between the enterprise and its supporting environment. This relationship between the public enterprise and the enabling system is seen as one of power-dependency, by adopting the interorganizational analysis approach.